Gearbox power loss. Part II: Friction losses in gears. (August 2015) - Fernandes, Carlos M.C.G.; Marques, Pedro M.T.; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: The second part of the study presents an extensive campaign of experimental tests in an FZG test rig. An average coefficient of friction between meshing gears was devised from the experimental results. Several aspects regarding the meshing gears power loss are discussed such as gear loss factor, coefficient of friction and the influence of gear oil formulation (wind turbine gear oils). Abstract : Highlights: Power loss in gears lubricated with wind turbine gear oils in FZG test rig. Comparison between numerical predictions and experimental results. Comparison of different gear loss factor formulations. Coefficient of friction between gear teeth for wind turbine gear oils.